The role of muslims in the 21st century - Fazli, Syed Ahmad Sibtain (Ferozsons Lahore, 2005)
The Role of Muslims in the 21st Century by Syed Ahmad Sibtain Fazli explores how Muslims can contribute to global society through values of compassion, justice, and knowledge, addressing challenges and opportunities in a modern, interconnected world.